The Use of Complementary and Alternative Medicine among Patients with Cervical Cancer Patients at H. Adam Malik Hospital Medan - Dhuha, Muhammad Hikmal; Ichwan, Muhammad; Lubis, Nenni Dwi Aprianti; Permatasari, Ranti (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: Cervical cancer is the second most common cancer in Indonesia. As a culturally rich country, Indonesia has various traditional medicines that are passed through generations to maintain health conditions as local wisdom in the society. A combination of conventional complementary and alternative medicine (CAM) is often used by cancer patients. This study aims to describe the use of complementary and alternative medicine among cervical cancer patients in H. Adam Malik Hospital Medan.Method: This is a descriptive observational study with a cross-sectional design. Subjects were patients diagnosed with cervical cancer at Gyneco-Oncology Clinic, H. Adam Malik Hospital, Medan. Fifty patients were interviewed with questions about the type, frequency, source of information, satisfaction rate, and openness to doctors regarding the use of CAM. Data were collected from July - September 2023.Results: The types of CAM used were nutritional therapy (39.3%), mind-body interventions (27.1%), herbs (23.4%), massage (9.3%), and acupuncture (0.9%). Most of the subjects used a combination of 2 types of CAM (74%). Most of the respondents (82%) were satisfied with CAM, and 48% of respondents did not inform doctors regarding the CAM used.Conclusion: All cervical cancer outpatients at H. Adam Malik Hospital used CAM together with conventional cancer therapy. The doctors should actively ask about the CAM that is used by the patients since not all patients disclose the information to their healthcare provider. Â